Boron-loaded liquid scintillator - Nemchenok, I.B.; Gundorin, N.A.; Kamnev, I.I.; Shevchik, E.A.; Shurenkova, A.A. (Functional Materials, 2013)
The high thermal neutron capture cross-section of ¹⁰B nucleus enables to use the boron-loaded organic scintillators as a basis of the neutron detectors. The study results of the new liquid scintillator with mass concentration of boron up to 6 %, based on linear alkylbenzene and contained as a boron additive ortho-carborane, are presented in the paper. The transparency spectra, scintillation characteristics of the new material and the detection efficiency for thermal neutrons have been studied.